Robot-assisted First Fib Resection for Neurogenic Thoracic Outlet Syndrome - Vancoillie Peter Jan; Wybaillie Elke; Maene Lieven; Beelen Roel (Annals of Musculoskeletal Medicine - Peertechz Publications, 2019)
Background: When conservative measures fail in the treatment of thoracic outlet syndrome (TOS), a first rib resection (FRR) is in order. Nowadays, a transaxillary or supraclavicular approach is most commonly used. However, both techniques have technical limitations. Objective: In this paper a minimal invasive, robot-assisted thoracoscopic technique tackling those shortcomings is proposed. Methods: A single-center retrospective study including 11 patients with 12 FRR's from January 2017 until August 2018 was performed. The main focus was the feasibility of this new technique by looking at mean hospital stay, postoperative pain and complication rate. Clinical outcome was evaluated at 6 weeks. Results: Twelve FRR were performed in 10 women and 1 man. Average operative time was 99 ± 32 minutes. One patient needed chest tube replacement for pneumothorax after initial tube removal. One patient was readmitted for pleurisy which was treated conservatively. Max average pain score (VAS; visual analogue pain score) was 5. Mean hospital stay was 3.4 days. Outcome at 6 weeks' time showed a complete relief of symptoms in 8 cases. Three patients had some residual fatigue complaints. However, these complaints improved over time. In one case there was no real benefit from the procedure. Conclusion: Robot-assisted thoracoscopic FRR is a safe and feasible method in the treatment of TOS with excellent postoperative results. A robot-assisted approach offers the benefit of an excellent exposure of the operative field and gentle handling of tissue. Further research in larger series is needed to compare this promising technique to conventional approaches.